Moving image and the museum: speculative spaces in 3 acts - Santos, Luísa (2022)
For the closing of Issue 4 of The Garage Journal, the author adopts one core methodology common to the practices of both film and curating: storytelling. All stories have a time, a space, and characters. Following the Rashomon effect, each one of the stories below could offer entirely different points on the relationships between the moving image and the museum. Similar to how a soundtrack can set a specific mood in film to heighten the emotional impact of the sights and sounds of a story, place and space can also serve to enhance the impact of characters (artworks) depicted in exhibitions, while characters can help to heighten the effect of events described in writing.